PENGEMBANGAN BAHAN AJAR MENULIS NARASI BERBASIS LITERASI WISATA LOKAL PADA KELAS IV SEKOLAH DASAR UNTUK MENINGKATKAN HASIL BELAJAR ASPEK KOGNITIF - Marlina; Abdul Muktadir; Bambang Parmadi (UNIB Press, 2023)
This study aims to determine the feasibility of the material, language, design, teacher and student responses, as well as the effectiveness of the product resulting from the development of narrative writing textbooks based on local tourism literacy to improve cognitive aspects of learning outcomes in elementary schools. This research is a Research and Development (R&D) research and the model used in the development of learning material is the ADDIE model. From the results, it is known that the results of the validation of the material, language, and design, as well as the responses of teachers and students to teaching materials are very feasible and well used in learning so that students are happy and interested in learning. The results of the effectiveness of teaching materials influenced students' understanding. Judging from the results of the significance value, p (=0.00) is smaller than (=0.05). Based on the gain-score test from the use of the e-module, it gives a moderate (68%) gain score. Therefore, students' understanding of teaching materials for writing narratives based on local tourism literacy was higher than students used textbooks from school.